Impact of educational intervention on dental students’ competence in managing injuries caused by sharp objects: a quasi-experimental study - Zarabadipour, Mahdieh; Gholizadeh, Negar; Mirzadeh, Monirsadat; Khorasani, Erfan (BMC medical education, 2025)
Sharp object injuries (SOI) pose significant risks to dental healthcare workers. This study evaluated the impact of an educational intervention on dental students' knowledge, attitudes, and practice habits regarding SOI management. A quasi-experimental before-after study was conducted among 87 dental students (59.8% female, 40.2% male; mean age: 23.45 years) in clinical years (DDS 2022-2025) at Qazvin University of Medical Sciences, Iran. Participants completed a validated 34-item questionnaire (10 knowledge, 7 attitude, 17 practice questions) before and after watching a 3-minute 36-second animated video on SOI management and post-exposure prophylaxis (PEP). Data were analyzed using SPSS 26 with chi-square, ANOVA, and Bonferroni correction (p < 0.0031). This study revealed significant differences in immediate post-injury performance knowledge (P = 0.001), PEP awareness (P = 0.025), and needle-capping (P = 0.001). However, there was no statistically significant difference in the extent of injury with sharp objects based on sex or age. There was a significant relationship between students' year of university entry and the extent of injury with a sharp object (P = 0.025). Most students (67.8%) did not know how to function correctly after a sharp object injury, and the highest number of sharp object injuries occurred in the 7th semester. Over 60% of injuries went unreported, primarily due to perceived insignificance (44.1%). Structured educational interventions, particularly visual aids, enhance SOI management knowledge. However, long-term behavioral changes and reporting compliance require further investigation. Integrating SOI training into dental curricula and fostering a culture of incident reporting are critical to mitigating risks.